Spatial and temporal bottom sediment characteristics of Pahang river estuary, Pahang, Malaysia - Abdurahman, Siti Waznah; Yunus, Kamaruzzaman; Ong, Meng Chuan; Zabri, Rina Sharlinda; Md Suhaimi, Mohd Zahir (Oriental Scientific Publishing Co., 2010)
Bottom sediment samples from Pahang river- estuary were analyzed for the sediment characteristics in order to understand better sedimentation processes in the estuary. The mean, sorting,skewness and kurtosis values of each sample were determined by the Moment’s method. This study showed that the sediment characteristics were not significantly differ (p > 0.05) with the seasonal changes, except for sorting (p < 0.05). The sediment mean size becomes finer towards the estuarine area with the range of very coarse sand to fine silt. This indicates that the characteristics of deposited sediments at each station are much dependant upon the combination of physical forces such as freshwater run-off, tidal currents and waves.